Decreasing Risk of Fatal Subarachnoid Hemorrhage and Other Epidemiological Trends in the Era of Coiling Implementation in Australia - Worthington, John Mark; Goumas, Chris; Jalaludin, Bin; Gattellari, Melina (Frontiers in Neurology, 2017)
Background and Purpose: Subarachnoid haemorrhage (SAH) is associated with a high risk of mortality and disability in survivors. We examined the epidemiology and burden of SAH in our population during a time services were re-organised to facilitate access to evidence-based endovascular coiling and neurosurgical care. Methods: SAH hospitalisations from 2001 to 2009, in New South Wales, Australia were linked to death registrations to June 30, 2010. We assessed the variability of admission rates, fatal SAH rates and case fatality over time and according to patient demographic characteristics. Results: There were 4,945 eligible patients admitted to hospital with SAH. The risk of fatal SAH significantly decreased by 2.7% on average per year (95% CI=0.3% to 4.9%). Case fatality at two, 30-days, 90-days and 365-days significantly declined over time. The average annual percentage reduction in mortality ranged from 4.4% for 30-day mortality (95% CI -6.1 to -2.7) (p<0.001) to 4.7% for mortality within two days (-7.1 to -2.2) (p<0.001) (Table 3). Three-percent of patients received coiling at the start of the study period, increasing to 28% at the end (p-value for trend<0.001). Females were significantly more likely to be hospitalised for a SAH compared with males (Incident rate ratio [IRR]=1.33, 95% CI=1.23-1.44) (P <0.001) and to die from SAH (IRR=1.40, 95% CI=1.24-1.59) (P<0.001). People born in South-East Asia and the Oceania region had a significantly increased risk of SAH, while the risk of fatal SAH was greater in South-East and North-East Asian born residents. People residing in areas of least disadvantage had the lowest risk of hospitalisation (IRR=0.83, 95% CI=0.74-0.92) and also the lowest risk of fatal SAH (0.81, 95% CI=0.66-1.00) (P<0.001 and P=0.003, respectively). For every 100 SAH admissions, 20 and 15 might be avoided in males and females, respectively, if the risk of SAH in our population equated to that of the most socio-economically advantaged. Conclusions: Our study reports reductions in mortality risk in SAH corresponding to identifiable changes in health service delivery and evolving treatments such as coiling. Addressing inequities in SAH risk and mortality, may require the targeting of prevalent and modifiable risk factors to improve population outcomes.